The Use of Mitochondria-Targeted Endonucleases to Manipulate mtDNA - Bacman, Sandra R. (Methods Enzymol, 2014)
For more than a decade, mitochondria-targeted nucleases have been used to promote double-strand breaks in the mitochondrial genome. This was done in mitochondrial DNA (mtDNA) homoplasmic systems, where all mtDNA molecules can be affected, to create models of mitochondrial deficiencies. Alternatively, they were also used in a heteroplasmic model, where only a subset of the mtDNA molecules were substrates for cleavage. The latter approach showed that mitochondrial-targeted nucleases can reduce mtDNA haplotype loads in affected tissues, with clear implications for the treatment of patients with mitochondrial diseases. In the last few years, designer nucleases, such as ZFN and TALEN, have been adapted to cleave mtDNA, greatly expanding the potential therapeutic use. This chapter describes the techniques and approaches used to test these designer enzymes.